SLEEP DISORDERS IN THE COVID-19 PANDEMIC: : NARRATIVE REVIEW - Sena de Lucena, Larissa; Ferreira Firmino, Fernanda; Emanuel Mendes da Silva Santos, Arlys; Thaine Teodoro, Danielly; Maria Senhorinha, Gláucia; Cerqueira Simões Braudes, Isadora (Health and Society, 2021)
Sleep is a biological need that can be affected by various factors and interferes with physical and mental well-being. Thus, the current pandemic of COVID-19 has changed the routine of a large part of the population, as well as affected the quality of sleep and has become a risk factor for the development of problems. In this context, the present study sought to highlight the importance of sleep quality for different situations. In view of this, the article understands how the current pandemic scenario has interfered with the quality of sleep and, consequently, with the population’s biopsychosocial paradigm. This is a bibliographic review with data collection from secondary sources in March and April 2021, carried out in the SciELO and PubMed databases. It has been observed that sleep deprivation makes it possible to increase cytokine activity, namely interferon (IFN), tumor necrosis factor alpha (TNF-α), interleukin-1-beta (IL-1-beta), favoring the increase in inflammatory markers such as C-reactive protein (CRP), this set of changes negatively affects immunity and is directly related to changes in sleep patterns. Therewith, from the analysis, it is possible to perceive the harm that the scenario of COVID-19 brought to the quality of sleep, causing several losses in daily activities. Therefore, it can be inferred that changes related to sleep contribute to the absence of alertness and changes in perception as well as in sensory processes, making the individual lethargic and with a reduction in the cognitive ability to perform functions of essential attributions for their quality of life.